Stable carbon and oxygen isotopes and element ratios of planktic foraminifer Neogloboquadrina dutertrei from sediment core M80/3_43 - Dirk Nürnberg; Nadine Gehre; Sebastian Fessler; Stefan Reissig (PANGAEA, 2025)
The subtropical Atlantic is affected by the Atlantic Meridional Mode (AMM) with its interannual and decadal impact on the rain intensity in Brazil and the Sahel zone as well as on hurricane activities in the Atlantic. The upwelling of cold water in the region of the Guinea Dome is also closely linked to the AMM dynamics. We here reconstruct the development of the Guinea Dome over the last two glacial/interglacial transitions (~156 kyrs). Our studies are based on gravity core M80/3-43, which was recovered from 4426 m water depth from the Cape Verde Archipelago area (southwest of Brava; 14°38.001 extquotesingleN 25°30.102 extquotesingleW) during the RV Meteor cruise M80/3 (URI:https://www.ldf.uni-hamburg.de/meteor/wochenberichte/wochenberichte-meteor/m80/m80-3-scr.pdf). The age model based on benthic foraminiferal oxygen stable isotopes (δ18O) and AMS radiocarbon dating is published by Eisele et al. (2015; https://doi.org/10.1016/j.margeo.2015.09.006). We use a planktonic foraminiferal multi-species isotope/geochemistry approach, combining high-resolution stable isotope (δ18O, δ13C) time series with elemental geochemistry (Mg/Ca), in order to address the surface to subsurface temperature and salinity development in relation to local upwelling phenomena and aftereffects on the NW African climate.